ML Lifecycle Canvas: Designing Machine Learning-Empowered UX with Material Lifecycle Thinking. (1st November 2020) - Zhou, Zhibin; Sun, Lingyun; Zhang, Yuyang; Liu, Xuanhui; Gong, Qing
ABSTRACT: As a particular type of artificial intelligence technology, machine learning (ML) is widely used to empower user experience (UX). However, designers, especially the novice designers, struggle to integrate ML into familiar design activities because of its ever-changing and growable nature. This paper proposes a design method called Material Lifecycle Thinking (MLT) that considers ML as a design material with its own lifecycle. MLT encourages designers to regard ML, users, and scenarios as three co-creators who cooperate in creating ML-empowered UX. We have developed ML Lifecycle Canvas (Canvas), a conceptual design tool that incorporates visual representations of the co-creators and ML lifecycle. Canvas guides designers to organize essential information for the application of MLT. By involving design students in the "research through design" process, the development of Canvas was iterated through its application to design projects. MLT and Canvas have been evaluated in design workshops, with completed proposals and evaluation results demonstrating that our work is a solid step forward in bridging the gap between UX and ML.